2019
DOI: 10.1002/ange.201900637
|View full text |Cite
|
Sign up to set email alerts
|

CsSbF2SO4: An Excellent Ultraviolet Nonlinear Optical Sulfate with a KTiOPO4 (KTP)‐type Structure

Abstract: A novel noncentrosymmetric (NCS) polar fluoride sulfate, CsSbF2SO4, was obtained by ionothermal synthesis. A meticulously designed co‐substitution approach was used to successfully replace the [TiO6]8− and [PO4]3− functional groups in KTiOPO4 (KTP) with [SbO4F2]7− and [SO4]2− units, respectively. The structure of CsSbF2SO4 features a pseudo‐3D framework consisting of interconnected 1D [SbF2O2SO4]5− chains of corner‐sharing [SbO4F2]7− octahedra and [SO4]2− tetrahedra. The title compound exhibits a sharply enlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…[26,[31][32][33][34][35][36][37][38], the cations with a stereoactive lone pair (Pb 2+ , Bi 3+ , etc.) [5,[39][40][41][42][43], d 0 transition-metal cations with second-order Jahn-Teller distortion (Ti 4+ , Nb 5+ , etc.) [15,44], or polar displacement of d 10 cation center (Zn 2+ , Cd 2+ , etc.)…”
Section: mentioning
confidence: 99%
“…[26,[31][32][33][34][35][36][37][38], the cations with a stereoactive lone pair (Pb 2+ , Bi 3+ , etc.) [5,[39][40][41][42][43], d 0 transition-metal cations with second-order Jahn-Teller distortion (Ti 4+ , Nb 5+ , etc.) [15,44], or polar displacement of d 10 cation center (Zn 2+ , Cd 2+ , etc.)…”
Section: mentioning
confidence: 99%
“…), and metal chalcogenide tetrahedral units. [13][14][15][16][17][18] We are especially interested in NLO materials based on metal germinates.R ecently,c ombination of GeO n (n = 4-6) polyhedra with borate clusters leads to as eries of metal borogermanates with good SHG properties, [19,20] among which Cs 2 GeB 4 O 9 shows the biggest SHG effect which is about 2.8 KDP. [20] Thec ombination of GeO 6 with Te O 6 octahedra produced several rosiaite-type compounds including MTeGeO 6 (M = Sr, Ba, Pb).…”
Section: àmentioning
confidence: 99%
“…[10][11][12][13] Regarding the sulphate, several sulphate-containing NLOs are newly recognized to show excellent SHG intensities in the UV region, for instance, Li 8 NaRb 3 (SO 4 ) 6 •2 H 2 O, (0.5 KDP), [14] NH 4 NaLi 2 (SO 4 ) 2 (1.1 KDP), [15] and CsSbF 2 SO 4 , (3.0 KDP). [16] However, the influence of the cationic moiety on NLO properties has long been neglected. Only a theoretical study on the hyperpolarizability of sodide Li(NH 3 )Na has been reported.…”
mentioning
confidence: 99%
“…Only a theoretical study on the hyperpolarizability of sodide Li(NH 3 )Na has been reported. [17a] Cations demonstrating the second-order Jahn-Teller effect are well known, [16,17] but such second-order Jahn-Teller cations are constituents of anionic moieties. For example, in CsSbF 2 SO 4 , the anionic moiety is formed by [SbO 4 F 2 ] 7À and [SO 4 ] 2À .…”
mentioning
confidence: 99%